Experiemental and simulation analysis of energy absorption capacity of 3D printed structure design - Soon, Elgin Kangwei (Nanyang Technological University, 2023)
With the vast improvement in technology over the years, industries are increasingly considering more modern manufacturing methods to reduce cost and time, while maintaining the standards of quality and consistency. One notable manufacturing method observed in the market is Three-Dimensional (3D) Printing, which is used widely in numerous applications, from toys to bio-tissues. The focus of this project is to analyse the provided 3D auxetic structure which has Kirigami technique involved, and test experimentally under simulated compressive and impact loads, for both vertical and horizontal orientations. The results from compression loading analysis reveals that the horizontally oriented model is capable of maintaining its auxetic performance with greater densification time. However, its vertically oriented counterpart has geometrical restrictions within the structure that subdued its auxetic behaviour. For impact loading, results have shown that the vertically oriented model could distribute stress more evenly within a fixed period of time, whereas the horizontally oriented model displayed marginally higher energy absorption capabilities, given its implicated spring-damping deformation behaviour upon impact. Hence, this study’s results could provide a new conceptual technique for the design and optimisation of lightweight energy absorption structures